THE EFFECTIVENESS OF PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT TO THE EIGHTH GRADE STUDENT OF SMP NEGERI 1 PEDAMARAN - Rizkia Berliana; Tahrun; Dewi Kartikasari (Esteem Journal of English Education Study Programme, 2024)
This research aims to compare students who receive learning through picture series with students who receive conventional teaching methods. learning recount text used picture series, determined the success of learning interest students' English. Teaching English in Indonesia is learners must be able to communicate with native speakers of the language and understood that English is used as a second language in some state sectors of the nation that function as bridges to other languages, such as trade and education. The research method used in This method is quantitative which used data collection techniques through pretest and post-test at SMP Negeri 1 Pedamaran. Based on this research, the picture series method was used. could have a significant positive impact on English learning, especially in English writing skills. Students become able to write. From the results of this research, students agree that used the series drew method could improve writing skills them, about recount text. the results of their writing practice through a picture series.